Optimalisasi Pembelajaran Al-Qur’an di TPQ Darut Taqwa Melalui Pendampingan Guru Dan Santri - Rijal Muhamad Kosim; Nuryamujiatun; Abdul Yazid (CV. Biha Cendekia, 2025)
Learning the Qur’an at the Taman Pendidikan Al-Qur’an (TPQ) plays a strategic role in shaping the character of young Muslims. However, observations at TPQ Darut Taqwa revealed several challenges, including limited teacher competence in applying interactive learning methods, varying student motivation, and minimal use of digital learning media. This community service program aims to optimize Qur’an learning through simultaneous mentoring of teachers and students. The method used was participatory mentoring with a descriptive qualitative approach, consisting of four stages: needs assessment, teacher training and student socialization, learning practice mentoring, and program evaluation. The results showed significant improvements: teacher competence increased by 36%, students’ Qur’an reading ability improved by an average of 40%, and students’ learning motivation increased, as indicated by an attendance rate rising from 65% to 90%. Furthermore, a more interactive and sustainable Qur’anic learning ecosystem was established. This activity proves that simultaneous teacher and student mentoring is effective in improving Qur’an learning quality and can be replicated in other TPQs.